2007
DOI: 10.1016/j.virol.2007.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne flavivirus infection in Ixodes scapularis larvae: Development of a novel method for synchronous viral infection of ticks

Abstract: Following a bite from an infected tick, tick-borne flaviviruses cause encephalitis, meningitis and hemorrhagic fever in humans. Although these viruses spend most of their time in the tick, little is known regarding the virus-vector interactions. We developed a simple method for synchronously infecting Ixodes scapularis larvae with Langat virus (LGTV) by immersion in media containing the virus. This technique resulted in approximately 96% of ticks becoming infected. LGTV infection and replication were demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 24 publications
1
63
0
Order By: Relevance
“…In addition, different concentrations of the initial TBFV inoculum may also affect TBFV replication kinetics in these organs. Mitzel et al showed that different concentrations for the LGTV inoculum affect the establishment of LGTV genome replication in I. scapularis larvae (30). Similarly, we suspect that different concentrations of the initial TBFV inoculum in female I. scapularis organ cultures could reveal varied levels of TBFV replication at different time points postinfection.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, different concentrations of the initial TBFV inoculum may also affect TBFV replication kinetics in these organs. Mitzel et al showed that different concentrations for the LGTV inoculum affect the establishment of LGTV genome replication in I. scapularis larvae (30). Similarly, we suspect that different concentrations of the initial TBFV inoculum in female I. scapularis organ cultures could reveal varied levels of TBFV replication at different time points postinfection.…”
Section: Discussionmentioning
confidence: 84%
“…ticks (30,60,61). Infectious LGTV and POWV were produced from all three infected tick organ cultures ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the ability of the viruses to infect and replicate in tick cells, infection of Vero and ISE6 cells was undertaken as previously described (Mitzel et al 2007). Both cell lines were initially infected with virus at a multiplicity of infection of 1, incubated at 348C or 378C, respectively, for 1 h, followed by addition of fresh maintenance medium.…”
Section: Virus Infection In Cell Culturementioning
confidence: 99%
“…Infection of ticks by the immersion method has been previously described (Mitzel et al 2007). Briefly, 60 larvae per group were collected in a sterile 1.5-mL screw cap centrifuge tube and pretreated by exposure to a reduced relative humidity.…”
Section: Virus Infection In Mosquitoes and Ticksmentioning
confidence: 99%